Effects of vortices on ion beam focusing in a plasma lens - Goncharov, A.A.; Gubarev, S.N.; Maslov, V.I.; Onishchenko, I.N. (Вопросы атомной науки и техники, 2001)
For high-current ion-beam focusing a vortical turbulence has been excited in plasma lens by the nonremovable gradient of an external magnetic field. The paper presents theoretical investigation, in the cylindrical approximation, of excitation of slow and fast vortices with taking into account the finite length of plasma lens. It is shown that the growth rate of vortix excitation decreases with decreasing the length of plasma lens. The spatial structures of the vortices are constructed. The expression for the vortex amplitude of saturation is derived.